2010
DOI: 10.1007/s11256-009-0148-8
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Inequitable Discipline Experiences of Urban Black Girls: Implications for Urban Educational Stakeholders

Abstract: There is a large body of research examining the discipline experiences of Black males (Lewis et al. in Souls: A Critical Journey of Black Politics, Culture, and Society, 2009; Skiba et al. in The Urban Review, 34, 317-348, 2002); however, less is known about the types of behavioral infractions Black female students exhibit and the discipline sanctions imposed for Black girls for such infractions. As a result, the purpose of this study is to examine the type of discipline infractions exhibited by Black female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
201
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(212 citation statements)
references
References 42 publications
7
201
0
2
Order By: Relevance
“…Traumatic experiences are common among adolescents (e.g., Finkelhor, Turner, Ormrod, & Hamby, 2009), yet teachers, administrators, and health professionals who lack trauma-informed training may misinterpret youths' responses to trauma (e.g., aggression), which can lead to harsher punishment or misdiagnoses without addressing youth's comorbid internalizing symptoms. This is particularly salient given the fact that African American girls receive more severe disciplinary actions than all other female students (Blake, Butler, Lewis, & Darensbourg, 2011) and are the fastest-growing population in the juvenile justice system (Crenshaw, Ocen, & Nanda, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic experiences are common among adolescents (e.g., Finkelhor, Turner, Ormrod, & Hamby, 2009), yet teachers, administrators, and health professionals who lack trauma-informed training may misinterpret youths' responses to trauma (e.g., aggression), which can lead to harsher punishment or misdiagnoses without addressing youth's comorbid internalizing symptoms. This is particularly salient given the fact that African American girls receive more severe disciplinary actions than all other female students (Blake, Butler, Lewis, & Darensbourg, 2011) and are the fastest-growing population in the juvenile justice system (Crenshaw, Ocen, & Nanda, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Wallace, Goodkind, Wallace, and Bachman (2008) reported that African American girls were over five times more likely than white girls to be suspended or expelled. A number of studies have shown high rates of disciplinary disparities for black females at both the elementary and secondary school levels (Blake, Butler, Lewis, & Darensbourg, 2011;Raffaele Mendez & Knoff, 2003;Toldson, McGee, & Lemmons, in press).…”
Section: Differential Effects: Who Is At Risk For Exclusionary Discipmentioning
confidence: 99%
“…Additionally, schools should work toward adopting alternatives to retention by embracing additional intervention strategies that could be beneficial to students, such as highly structured after‐school and summer programming and increased academic and behavioral supports provided through a multitiered system of supports (MTSS; Bowman, ; Jimerson et al, 2006). Furthermore, supporting the implementation of school‐wide positive behavioral interventions and supports (SWPBIS) within an MTSS framework is important for preventing behavior problems before they occur (Blake, Butler, Lewis, & Darensbourg, ; National Association of School Psychologists, ; Skiba et al, ).…”
Section: Discussionmentioning
confidence: 99%